Women and partners’ experiences of critical perinatal events: a qualitative study - Marianne Johansen; Jette Led Sørensen; Stinne Høgh; Laura Emdal Navne; Mette Nordahl Svendsen (BMJ Open)
Objective The aim of this study was to explore women and partners’ experiences following critical perinatal events.Design This is a qualitative interview study. We conducted semistructured individual interviews with women and their partners in separate rooms. Interviews were analysed thematically and validated by a transdisciplinary group of anthropologists, obstetricians and a midwife.Setting Department of obstetrics at a tertiary referral university hospital in Denmark.Participants Women and partners who had experienced a critical perinatal event within the past 3–12 months.Results We conducted 17 interviews and identified three main themes: (1) ambivalence towards medicalisation, (2) the extended temporality of a critical birth and (3) postnatal loss of attention from healthcare professionals. Overall, participants expressed a high degree of trust in and quality of provided healthcare during the critical perinatal events. They experienced medicalisation (obstetric interventions) as a necessity, linking them to the safety of the child and their new role as responsible parents. However, some women experienced disempowerment when healthcare professionals overlooked their ability to stay actively involved during birth events. Postnatally, women and their partners experienced shortages of healthcare professional resources, absent healthcare and lack of attention.Conclusions Women and their partners’ experiences of critical perinatal events begin long before and end long after the actual moment of childbirth, challenging conventional ideas about the birth as being the pivotal event in making families. In future healthcare planning, it is important to to align expectations and guide parental involvement in birth events and to acknowledge the postnatal period as equally crucial.